Factors That Influence the Interest in Becoming an Investor in the Capital Market - Irine Herdjiono; Jumiati Jumiati (Jurnal Economia, 2022)
AbstractThis study aims to examine factors that influence students' interest in becoming investors in the capital market. Factors to be tested include minimum capital, investment risk, perception of return, and financial literacy. The number of samples used is 360 respondents selected using a simple random sampling technique. This quantitative research used primary data; a questionnaire was measured using a Likert scale and binary logistic regression analysis. The results showed that minimum capital and investment risk had a negative and significant influence on the investor’s interest, perception of return had no effect on the investor’s interest, and financial literacy had a positive and significant effect on the investor’s interest. Therefore, the limited funds owned by students should be a concern to increase the interest of Millenials to invest in the capital market and improve education about financial literacy. Keywords: minimum capital, investment risk, financial literacy Faktor-Faktor yang Mempengaruhi Minat Menjadi Investor di Pasar Modal AbstrakPenelitian ini bertujuan untuk mengkaji faktor-faktor yang mempengaruhi minat mahasiswa untuk menjadi investor di pasar modal. Faktor-faktor yang akan diuji antara lain modal minimum, risiko investasi, persepsi pengembalian, dan literasi keuangan. Jumlah sampel yang digunakan adalah 360 responden yang dipilih dengan menggunakan teknik simple random sampling. Penelitian ini merupakan penelitian kuantitatif dengan menggunakan data primer yaitu kuesioner yang diukur menggunakan skala likert dan analisis regresi logistik biner. Hasil penelitian menunjukkan bahwa modal minimum dan risiko investasi berpengaruh negatif dan signifikan terhadap minat investor, persepsi pengembalian tidak berpengaruh terhadap minat investor, dan literasi keuangan berpengaruh positif dan signifikan terhadap minat investor. Keterbatasan dana yang dimiliki oleh mahasiswa harus menjadi perhatian untuk meningkatkan minat kaum milenial untuk berinvestasi di pasar modal dan peningkatan program literasi keuangan perlu ditingkatkan. Kata kunci: modal minimum, risiko investasi, literasi keuangan